Development of an Electronic Controller Applied to a Robotized Manipulator - Urrea-Onate, E; Kern-Molina, J (Elsevier Ltd, 2016)
The design and implementation of an embedded control system using DSC (Digital Signal Controller) devices of the dsPIC type, applied on a four-DOF (Degrees Of Freedom) model OWI-535 robotic manipulator is presented. A control structure based on a Master/Slave configuration between two dsPIC30F4013 through the SPI (Serial Peripheral Interface) protocol is developed. In such a system, algorithms are implemented: PID (Proportional Integral Derivative) with anti-windup, and generation PWM (Pulse-Width Modulation) and data acquisition, in the DSC master and slave, respectively. The proposed methodology greatly simplifies the development of an autonomous control system based on DSCs that communicate with each other. Taking advantage of the high transmission speed of SPI communications and of the quick response of the dsPIC30F4013 DSC which makes up the embedded system, it is possible to reduce the correction time error of the robot s joint position and to eliminate the vibrations of the actuators, achieving settlement of the desired position quickly and smoothly. © 2016